ANALISIS RISIKO PRESERVASI JALAN SP. TOHPATI – TAMPAK SIRING – ISTANA PRESIDEN, KABUPATEN GIANYAR, PROVINSI BALI - Widyantari, I Gusti Ayu; Agustawijaya, Didi Supriadi; Murtiadi, Suryawan (JURNAL SPEKTRAN; Vol 6 No 1 (2018): Vol. 6, No. 1, Januari 2018, 2018)
Road Preservation Project Sp. Tohpati - Tampak Siring - Presidential Palace, Gianyar Regency is implemented to reduce congestion, to shorten travel time and to smoothen the traffic flow from Denpasar city to Gianyar regency especially to the Presidential Palace. Risks may occur during the construction period of this project. This study aims to identify, analyze, mitigate and allocate risk, so it can be used as a basis for decision-making by related parties to overcome the negative impacts that occur. This research was used qualitative and quantitative methods. Data was collected through a questionnaire survey. Risk was analysieds using quantitative method by identifying the dominant risks. The identified dominant risks obtained were analyzed using the Analitycal Hierarchy Process (AHP) method to rank the dominant risks based on its urgency of treatment. The results showed that 11 (eleven) sources of risk obtained risk acceptability for unacceptable, undesirable, acceptable, and negligible with the percentage of 11.76%, 16.18%, 47.06% and 25.00 respectively %. The results shows that the dominant/major risks covers lack of qualified and competent project workforce resulting in poor job quality, the presence of workers who do not use safety equipment while working, and fatigue due to the large number of work done at night (asphalting work). The rank of priorities based on the greatest weight resulted from AHP analysis includes are project, technical, safety, human, economic and financial risks, and finally political / regulatory risks respectively. Contractor is the party most responsible for the risks that occur. Keywords: Risk, road preservation, SPSS, AHP